Sarkofagus Ampelan Wringin: Data Baru Tradisi Megalitik Di Bondowoso - Diman Suryanto (Balai Arkeologi Yogyakarta, 2004)
The sarcophagi in Java and Bali, apart from providing material for knowledge of past religious customs and ideals, also bring up problems that still have to be resolved. The era of making sarcophagi, as determined by Van Stein Callenfels and Van Heekeren, fell during the development of the bronze culture in Indonesia. It was at this time that the manufacture of iron objects was also known, as evidenced by discoveries in the sarcophagus. This determination of the period of development is reinforced by other evidence, namely the shape of the protrusion of the head, the protruding facial features of the sarcophagus, with long ears, very similar to the decorative pattern of the bronze nekara mask.